Knowledge management in the project life cycle: Initial research on Polish SMEs - Iwona Łapuńka; Iwona Pisz (Foundations of Management, 2014)
Contemporary organizations run their activities in an environment, which might be defined as fully uncertain and turbulent. Due to variations that occur in the surrounding environment, an increased attention of management practitioners and theoreticians is paid to new management concepts frequently in an integrated version. The authors express a deep belief that consolidation of approaches to project management and knowledge management constitutes a response to challenge for modern organizations. Research into the issue was based on an attempt to determine significance of the knowledge management issue in a life of projects performed by Polish small and medium-sized enterprises (SMEs). Systemizing of desired knowledge management results in a project, from the point of view of its crucial success factors, is essentially substantiated in providing success of projects performed.Preliminary research included SMEs in construction engineering industry. The enterprises perform project- driven orders or apply a project approach in economic activities that they execute. Research conducted by the authors so far, implies, that the SME sector is characterized by a particularly low efficiency in project management. Hypothetic assumptions indicate that one of the main reasons of reaching an unsatisfactory level of project proficiency shaped mainly by processes of synchronizing and coordination of project activities, is an insufficient level of development of social, organization and technological systems and methods of capitalization, as well as transmission of useful project management knowledge.Essential function is performed by a group of selected respondents - 25 enterprises from the group of SMEs, including 5 micro enterprises, 12 small enterprises, and 8 medium-sized enterprises. Analyses performed so far, take into consideration the economic situation of SMEs in Poland.
Keywords: 650; project management; knowledge management; project life cycle; Polish SMEs sector; construction engineering industry